Research in Counselling Psychology: Changing Emphases in a Canadian Perspective - Lecomte, Conrad; Dumont, Florent; Zingle, Harvey W. (Canadian Journal of Counselling and Psychotherapy, 2012)
This article defines counselling psychology and the factors which shaped its de- velopment. It then presents a brief survey of contemporary research in this discipline within a tripartite schema: remediation, developmental counselling, and prevention. Methodological issues are then addressed that focus on designs and trends; this forms the basis for establishing principles of, and formulating concrete suggestions for future research. Finally, within a Canadian context, operational research support is assessed, recommendations for areas of expanded research are offered, and pro- posals for broader operational support are presented.